Attitude, self-esteem, and mathematics performance of the students in a collaborative learning environment - Makilan, Novemay C. (Edelweiss Applied Science and Technology, 2025)
To develop 21st century competencies, it is crucial to comprehend multiple factors that influence students' mathematics performance. Collaborative learning is a key factor in boosting self-esteem, leading to better academic results. This study explores students' attitudes toward collaborative learning, their self-esteem in learning mathematics, and their mathematics performance. It also investigates the mediating role of self-esteem between students' attitudes and their mathematics performance and the moderating role of specialization in the relationship between self-esteem and performance. A descriptive-correlational research design was employed, utilizing regression, mediation, and moderation analyses to interpret the data. The sample comprised 64 second-year Industrial Technology students specializing in Architectural Drafting, Automotive Technology, and Electrical Technology. Findings revealed that students exhibited a very positive attitude toward collaborative learning, reported high levels of self-esteem, and demonstrated average mathematics performance. Self-esteem has a significant predictive relationship with mathematics performance. While the attitude toward collaborative learning does not directly influence mathematics performance, it exerts a significant indirect effect through self-esteem. Furthermore, specialization does not moderate the relationship between self-esteem and mathematics performance. Therefore, self-esteem is crucial in students' mathematics performance, as it bridges the gap between collaborative learning attitudes and academic results, regardless of specialization. The need to promote collaborative environments and improve students' self-esteem is recommended to achieve better mathematics outcomes.